"Keeping it on your radar"—assessing the barriers and facilitators to a timely diagnosis of type 1 diabetes in childhood: A qualitative study from the early detection of type 1 diabetes in youth study. Issue 1 (18th December 2017) - Townson, Julia; Gallagher, Dunla; Cowley, Laura; Channon, Susan; Robling, Michael; Williams, David; Hughes, Clare; Murphy, Simon; Lowes, Lesley; Gregory, John W.
Summary: Aims: The aim of this study was to explore from the perspectives of key stakeholders involved in the pathway to diagnosis, the barriers and facilitators to a timely diagnosis of type 1 diabetes in childhood. Methods: Qualitative interviews and free‐text analyses were undertaken in 21 parents with a child diagnosed with type 1 diabetes, 60 parents without a child diagnosed with type 1 diabetes, 9 primary healthcare professionals, 9 teachers and 3 community diabetes liaison nurses. Data were analysed thematically and 30% double coded. Results: Two key themes were identified, namely the importance of widespread awareness and knowledge and seeking healthcare professional help. Parents with a child diagnosed with type 1 diabetes described seeking opinions from a number of individuals prior to seeking health professional help. Healthcare professionals recognized the rarity of the condition and the need for it to be kept on their "radar", to ensure they considered it when examining an unwell child. The process of obtaining a primary healthcare appointment was identified as potentially playing a crucial role in the diagnostic process. However, most parents with a child diagnosed with type 1 diabetes described receiving an appointment on the day they sought it. Conclusions: Knowledge and awareness of type 1 diabetes in childhood remain limited in the general population and misconceptions persist relating to how children present with this serious condition. An effective community‐based intervention to raise awareness amongst key stakeholders is required to ensure children receive a timely diagnosis once symptomatic. Abstract : This study explores the perspectives of key stakeholders involved in the pathway to diagnosis of type 1 diabetes (T1D) in childhood. Qualitative data were collected from parents with and without a child diagnosed with T1D, primary care health professionals, teachers and community diabetes liaison nurses. Results identified two main themes, the importance of widespread awareness/knowledge and seeking health professional help.